Development of the Tendency to Use Emotion Regulation Strategies and Their Relation to Depressive Symptoms in Chinese Adolescents - Sai, Liyang; Luo, Sichen; Ward, Anne; Sang, Biao (Frontiers in Psychology, 2016)
The process model of emotion regulation posits that the tendency to use cognitive reappraisal is associated with positive outcomes (e.g., greater positive emotion) while the tendency to use expressive suppression is associated with adverse outcomes (e.g., greater negative emotion). Many studies using adult samples support this theory. However, the development of the tendency to use cognitive reappraisal/expressive suppression and how these tendencies relate to depressive symptoms in adolescents remain unclear. To address these questions, 639 Chinese adolescents aged 12–18 years old were asked to report their tendency to use cognitive reappraisal/expressive suppression as well as their depressive symptoms. General linear model multivariate analysis of variance showed a statistically significant age effect for the tendency to use emotion regulation strategies. Further analysis found that these adolescents reported using less expressive suppression as age increased, while there was no age effect for the tendency to use cognitive reappraisal. Moreover, linear regression analysis revealed that the tendency to use cognitive reappraisal in daily life negatively influenced depressive symptoms, while the tendency to use expressive suppression in daily life positively influenced depressive symptoms. These findings provide evidence that support the development of emotion regulation strategies in childhood and adolescence.